Disarmament, peace and development - Braun, Reiner, 1952-; Archer, Colin, 1952-; Breines, Ingeborg; Chatterji, Manas, 1937-; Skiljan, Amela (Contributions to conflict management, peace economics and development, 2018)
Excessive military spendingreduces the available financial reserves for health,education, and other human needs. For poor countries, it increases poverty, unemployment, and destitution.It also strengthens dictatorial tendencies in politics and acts against democratic values. If we want to achieve peace, eliminate poverty, decrease inequality, and achieve social justice, we should devote all our energies to reducing military spending and using the released resources for economic development. For that, we need a concerted effort to encourage disarmament. This newvolume provides reflections and insights from leading public figures and activists who oppose military expenditure in any form. Many of the contributions to this volume were presented as speeches at the 'Disarm! For a Climate of Peace' meeting held in Berlin in 2016, organized by the International Peace Bureau. The volume also includes additional research-oriented chapters to complement the transcripts from the International Peace Bureau meeting.